2010
DOI: 10.4161/cib.3.2.10584
|View full text |Cite
|
Sign up to set email alerts
|

The rhizobacterial elicitor acetoin induces systemic resistance inArabidopsis thaliana

Abstract: The majority of plant growth promoting rhizobacteria (PGPR) confer plant immunity against a wide range of foliar diseases by activating plant defences that reduce a plant's susceptibility to pathogen attack. Here we show that Arabidopsis thaliana (Col-0) plants exposed to Bacillus subtilis strain FB17 (hereafter FB17), results in reduced disease severity against Pseudomonas syringae pv. tomato DC3000 (hereafter DC3000) compared to plants without FB17 treatment. Exogenous application of the B. subtilis derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(132 citation statements)
references
References 63 publications
2
124
1
2
Order By: Relevance
“…In both as well as three genes that are part of the biosynthetic pathway for acetoin and 2,3-butanediol, indicating the possible production of these compounds by the strain. These compounds can act as nutrient source as well as plant growth-promoting molecules (Ryu et al, 2003;Rudrappa et al, 2010), which might facilitate the interaction with algal hosts. Genes for the complete multi-peptide urease (ureA-G; PGA2_c31970-c32030) and three genes probably coding for surface antigens (PGA2_c18820-PGA2_c18840) are also unique in strain 2.10.…”
Section: Resultsmentioning
confidence: 99%
“…In both as well as three genes that are part of the biosynthetic pathway for acetoin and 2,3-butanediol, indicating the possible production of these compounds by the strain. These compounds can act as nutrient source as well as plant growth-promoting molecules (Ryu et al, 2003;Rudrappa et al, 2010), which might facilitate the interaction with algal hosts. Genes for the complete multi-peptide urease (ureA-G; PGA2_c31970-c32030) and three genes probably coding for surface antigens (PGA2_c18820-PGA2_c18840) are also unique in strain 2.10.…”
Section: Resultsmentioning
confidence: 99%
“…Among these PGPR strains, FB17 rhizoinoculated onto the roots of Arabidopsis plants reduced disease severity, thus inhibiting the proliferation of foliar pathogen Pst DC3000 through induction of JA/ET-mediated ISR and SAmediated SAR (Rudrappa et al, 2010). The magnitude of colonization on the root by beneficial microbes is limited by several factors that include root surface biochemistry and composition of root exudates (Rudrappa et al, 2008a;Doornbos et al, 2011;Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This recent data validates the specificity and preference of B. subtilis for MA. Our previous studies showed that aerial plant pathogenesis involved the induction of MA in root secretions that effectively recruited beneficial rhizobacteria (Rudrappa et al, 2008a(Rudrappa et al, , 2010. We also showed that the pathogenic phyllosphere pathogen, Pst DC3000, induced root ALMT1 expression (Rudrappa et al, 2008b).…”
Section: Foliar Mamps Trigger Root Fb17 Colonizationmentioning
confidence: 99%
See 2 more Smart Citations